Foraging behavior of Argentine Criollo and Angus cows grazing semi-desert rangelands in the Arid Gran Chaco region of Argentina - Herrera Conegliano, Oscar Ariel (2022)
We monitored grazing behavior and habitat selection of Argentine Criollo (AC), South American heritage cattle breed, and Angus (AA) cows during summer and winter of 2016 (wetter year) and 2017 (drier year) at a site in La Rioja, Argentina. In each year and season, five AC and five AA cows were fitted with GPS collars configured to log animal position at 10-min intervals for 40 days. Movement, activity, and vegetation use patterns of each breed were derived from the GPS data. In summer, AC cows traveled similar daily distances, explored smaller (wetter year) or slightly larger (drier year) areas of the pasture, tended to move along more sinuous path trajectories, and showed stronger selection of the vegetation unit with higher forage quality and lowest woody cover compared to AA counterparts. AC cows allocated similar (wetter year) or more time to graze (drier year), allocated roughly the same amount of time to travel, and spent similar (wetter year) or less time resting (drier year) than AA cows. In winter, foraging behavior differences between breeds were only observed in the drier year. AC cows traveled farther and spent less time resting than AA counterparts that year. When comparing summer vs. winter movement patterns of each breed, AC cows showed an apparent greater ability to adapt to changing forage conditions (foraging plasticity) compared to AA counterparts which appeared to exhibit more rigid foraging patterns. Criollo cattle could be a tool to increase the resilience of Arid Chaco beef systems in the face of climate change. The rangeland conservation implications of raising Criollo vs. British beef cattle require further investigation.